1979
DOI: 10.1113/jphysiol.1979.sp012821
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the atrial receptors responsible for a reflex increase in heart rate in the dog.

Abstract: SUMMARY1. In dogs anaesthetized with chloralose, small latex balloons were positioned at the left pulmonary vein-atrial junctions so as to stretch this region. By recording action potentials from slips of the cervical vagi it was established that distension of these balloons stimulated receptor endings in the atrial endocardium which discharged into the myelinated branches of the vagi i.e. Paintal type A, type B and Intermediate type receptors.2. In other dogs, cooling the cervical vagus in steps of 2 'C reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 23 publications
10
66
0
Order By: Relevance
“…At a temperature of 8-12 'C increases in the frequency of discharge, associated with atrial distension, in myelinated and some non-myelinated afferent fibres are blocked (Kappagoda, Linden & Sivanathan, 1979); and some vagal efferent fibres may also be blocked. It was therefore of interest to discover that vagal cooling by itself led to a significant rise of plasma AVP concentration (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…At a temperature of 8-12 'C increases in the frequency of discharge, associated with atrial distension, in myelinated and some non-myelinated afferent fibres are blocked (Kappagoda, Linden & Sivanathan, 1979); and some vagal efferent fibres may also be blocked. It was therefore of interest to discover that vagal cooling by itself led to a significant rise of plasma AVP concentration (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed on twenty dogs weighing 18-28 kg which were given a subcutaneous injection of morphine sulphate (0 5 mg. kg-') and subsequently anaesthetized with chloralose and artificially ventilated with oxygen-enriched air (40% 02) as described by Kappagoda et al (1979). During recording of the activity in renal nerves, the animals were given gallamine triethiodide (initial dose 2 mg. kg-'; subsequent doses 1 mg. kg-') as described by Linden et al (1980); periodically doses of gallamine triethiodide were omitted and the animal allowed to recover from its effects so as to gauge the depth of anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Karim, Kidd, Malpus & Penna (1972) provided direct evidence for an increase in activity in efferent cardiac sympathetic nerves in response to stimulation of atrial receptors and a reflex reduction in activity in efferent renal sympathetic nerves. Subsequently both the reflex increase in heart rate and the reflex reduction in activity in renal nerves were shown to involve only atrial receptors attached to myelinated vagal fibres (Kappagoda, Linden & Sivananthan, 1979;Linden, Mary & Weatherill, 1980). Carswell, Hainsworth & Ledsome (1970) observed that the magnitude of the reflex increase in heart rate was unaltered by changes in pressure in the carotid sinuses implying little or no influence of changes in discharge of carotid sinus baroreceptors on this response.…”
Section: Introductionmentioning
confidence: 99%
“…The vagi were cooled in the neck using a silver thermode, the details of which have been described previously (Kappagoda, Linden & Sivananthan, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…In all experiments the cervical vagi were cooled by a thermoelectric module (see Kappagoda et al 1979 for details). In seven dogs the vagi were cooled to a temperature of 6-8 'C and in one dog to a temperature of 3 TC.…”
Section: Effect Of Cold Blockade Of the Cervical Vagi On The Responsesmentioning
confidence: 99%